2019
DOI: 10.1093/jac/dkz007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with integrase inhibitors in HIV-2-infected individuals in Spain

Abstract: Background: HIV-2 is a neglected virus despite estimates of 1-2 million people being infected worldwide. The virus is naturally resistant to some antiretrovirals used to treat HIV-1 and therapeutic options are limited for patients with HIV-2. Methods: In this retrospective observational study, we analysed all HIV-2-infected individuals treated with integrase strand transfer inhibitors (INSTIs) recorded in the Spanish HIV-2 cohort. Demographics, treatment modalities, laboratory values, quantitative HIV-2 RNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…For instance, amino acid insertions at position 231 emerged in a subset of HIV-2 patients during INI-based treatment, and HIV-2 isolates containing these insertions exhibited low-level cross-resistance to bictegravir in culture (34). Similar insertions were reported in an SIV mac251 -infected rhesus macaque that was treated with long-acting cabotegravir (53) and in an HIV-2-infected patient who received raltegravir followed by dolutegravir-based ART (54). In the future, it will be important to determine the effects of both established and novel mutations on clinical responsiveness to bictegravir, as well as other second-generation INIs, in larger numbers of HIV-2-infected individuals.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…For instance, amino acid insertions at position 231 emerged in a subset of HIV-2 patients during INI-based treatment, and HIV-2 isolates containing these insertions exhibited low-level cross-resistance to bictegravir in culture (34). Similar insertions were reported in an SIV mac251 -infected rhesus macaque that was treated with long-acting cabotegravir (53) and in an HIV-2-infected patient who received raltegravir followed by dolutegravir-based ART (54). In the future, it will be important to determine the effects of both established and novel mutations on clinical responsiveness to bictegravir, as well as other second-generation INIs, in larger numbers of HIV-2-infected individuals.…”
mentioning
confidence: 73%
“…Through the inclusion of emtricitabine and tenofovir alafenamide, Biktarvy meets the requirements for treatment of HIV-infected patients who are coinfected with hepatitis B virus (55), which represents ϳ10% of all people living with HIV in West Africa (56)(57)(58)(59). Based on findings from our group and others, all three antiretroviral components of Biktarvy are fully active against HIV-2 in vitro (19,(60)(61)(62)(63), although we emphasize that published information regarding the use of tenofovir alafenamide for HIV-2 treatment is limited to five patients (54). Taken together, the available data suggest that a clinical trial should be performed in West Africa to determine the effectiveness of Biktarvy as first-line ART for all HIV-infected individuals, including those infected with HIV-2.…”
mentioning
confidence: 94%
“…Effective drugs against HIV-2 are reported in Table 2. In particular, recent evidence has confirmed the potency of integration inhibitors on wild HIV-2 clinical isolates, suggesting that integrase strand transfer inhibitor (INSTI)-based combinations are effective and safe treatment options for these individuals [24,70,80,81].…”
Section: Treatment and Resistancementioning
confidence: 99%
“…Despite the fact that INSTI-based regimens are an effective therapeutic resource, it is important to underline that mutations in INSTI resistance have led to being frequently selected in failing patients [80,81].…”
Section: Maturation Inhibitors Bevirimatmentioning
confidence: 99%
“…Broadly, this evidence has shown that HIV-2 is resistant to non-nucleoside reverse transcriptase inhibitors (NNRTIs) [10], shows decreased susceptibility to some protease inhibitors (PIs) [11,12], and is susceptible to a variety of nucleoside reverse transcriptase inhibitors (NRTIs), boosted PIs, and integrase inhibitors [13]. Recent data indicate that the integrase strand transfer inhibitor (INSTI) class of integrase inhibitors are safe and effective against HIV-2 [14,15]. While reports suggest that boosted PI-containing regimens perform better that triple NRTI regimens [16], it has been challenging to identify a preferred initial ART regimen for patients with HIV-2 [17] which is reflected by comparatively poor responses to treatment among those patients.…”
Section: Introductionmentioning
confidence: 99%